s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Genetic differences between the endangered San Clemente Island loggerhead shrike Lanius ludovicianus mearnsi and two neighbouring subspecies demonstrated by mtDNA control region and cytochrome b sequence variation - N. I. Mundy; C. S. Winchell; D. S. Woodruff (Molecular Ecology, 1997)
We investigated mtDNA sequence variation in five populations of the loggerhead shrike Lanius ludovicianus , representing four subspecies, including the San Clemente loggerhead shrike L. l. mearnsi , a critically endangered California Channel Island endemic. Variability in 200 bp of control region and 200 bp of cytochrome b was extremely low, and defined four haplotypes. Strong structure was apparent among all three southern Californian subspecies, including L. l. mearnsi , with one haplotype predominating in each subspecies. Although potential levels of gene flow between L. l. mearnsi and neighbouring populations are low, mtDNA data support field observations that some shrikes visit the island during winter but do not stay to breed, and suggest that these birds come from the mainland. The similarity in haplotypes between populations from Saskatchewan, Canada and those in southern California suggests post‐glacial northern range expansion of the species. Our results confirm the evolutionary distinctiveness of L. l. mearnsi and justify continuing efforts for its conservation.